Promoting COVID-19 Vaccine Acceptance through Community Engagement: An Ethnographic Study in Ghana - Matilda Aberese-Ako; Wisdom Ebelin; Phidelia Theresa Doegah; Mawulom Kuatewo; Lebene Kpodo; Atsu Godsway Kpordorlor; Robert Kaba Alhassan; Atubiga Alobit Baba; Senanu Djokoto; Evelyn K. Ansah (Hindawi Limited, 2023)
Introduction. To successfully manage COVID-19 and to meet the target of vaccinating 22.9 million people in Ghana, the government has adopted community engagement as one of the strategies. Yet, the Volta Region continues to record the lowest rate of vaccine acceptance in Ghana. This study explored how government institutions engaged communities on COVID-19 vaccine preparedness and acceptance in two administrative municipalities in Ghana. Methods. This qualitative study employed face-to-face in-depth interviews among thirty-six respondents comprising of government officials and community leaders and ten focus group discussions among 87 people made up of men and women most of whom were natives and some migrants in two administrative municipalities in Ghana. Data were collected from June to September 2021. Audio interviews were transcribed and uploaded to Nvivo 12 to support triangulation, coding, and thematic analysis. Ethical approval was obtained from the requisite authority, and all COVID-19 restrictions were observed. Results. Government institutions focused on informing communities of vaccines and vaccination with little input from the communities. The Ghana Health Service carried out the most extensive engagement because they had more decentralized institutions. Successful engagement activities resulted in vaccine acceptance among some community members. Challenges in community engagement included insufficient logistics and myths and misconceptions about vaccines, which accounted for some community members' lack of trust in vaccines, resulting in their unwillingness to vaccinate. Government officials used innovative approaches such as comparing the safety of COVID-19 vaccines to vaccines designed for children under the age of five years to deal with misinformation. Conclusion. Government needs to provide more resources to institutions that are mandated to carry out engagement activities to enable them carry out their tasks. It is further recommended that government institutions should intensify community engagement in distant communities to support the country to meet the target.